PENINGKATAN POTENSI CEKER BROILER HASIL SAMPING DARI TEMPAT PEMOTONGAN AYAM (TPA) MENJADI GELATIN DENGAN MENGGUNAKAN METODE EKSTRAKSI TERKOMBINASI - Miwada, I Nyoman Sumerta; Simpen, I.N. (Bumi Lestari, 2009)
This research was proposed to increased the potency of shanks, esspeciality their skin by hidrolising the collagen (by extrating with solvent) into gelatine products. This research was run on a Completely Randomized Design (CRD). The experiment was run in factorial designs of 2 x 3. Factor I was solven type chloroform-ethanol and heksana-etanol, Factor II was a combination of ratio of 1:1, 1:3, and 3:1. The variable in this research were pH, viscosity, rendement, protein, and fat of gelatine contents. Result of the research indicated that the pH value of gelatine was between 8.21-8.52. The solvent of chloroform-ethanol gave the best result (P<0.05) on the ratio of 1:3. Percentage of rendement of gelatine was highest obtained from chloroform-ethanol types compared with that of hexane-ethanol (P<0.05). The interaction combinations of chloroform-ethanol on the ratio of 1:1 would result in the rendement percentage to be higher than others (P<0.05). Otherwise, the solvent of hexane-ethanol might bring impact to the viscocity of gelatine (P<0.05) compared to chloroform-ethanol. The interaction combination of hexane-ethanol ratio gave the best result (P<0.05) with highest level of viscosity on the ratio of 3:1 and lower on 1:3. The content of gelatine protein was highest (P<0.05) for the combination of hexane-ethanol compared to that of chloroform-ethanol. The solvent of chloroform-ethanol types could degrade more component of gelatine fat (P<0.05) compared to that of hexane-ethanol. It could be concluded that the research that the content of gelatine protein from extraction by hexane-ethanol on the combination ratio of 3:1 brought the highest quality compared to others.
Keywords: shanks; by product; protein collagen; extraction; gelatine